1989
DOI: 10.1123/pes.1.4.336
|View full text |Cite
|
Sign up to set email alerts
|

Resistance Training and Youth

Abstract: The use of resistance training for children has increased in popularity and interest. It appears that children are capable of voluntary strength gains. Exercise prescription in younger populations is critical and requires certain program variables to be altered from adult perspectives. Individualization is vital, as the rate of physiological maturation has an impact on the adaptations that occur. The major difference in programs for children is the use of lighter loads (i.e., > 6 RM loads). It appears that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
1
6

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 38 publications
(56 reference statements)
2
50
1
6
Order By: Relevance
“…However, in contrast to this previous study, similar changes were observed in both the SUP and UN-SUP groups. Considering the age of the subjects in the present study, it seems reasonable to suggest that some of the increase in the body mass measures in both groups of the present study was due to normal changes associated with puberty (15,17). Maturation effects may also partially explain why the relative changes in strength and power in the present study are greater than those previously reported in experienced strength trainers (19).…”
Section: Discussioncontrasting
confidence: 56%
“…However, in contrast to this previous study, similar changes were observed in both the SUP and UN-SUP groups. Considering the age of the subjects in the present study, it seems reasonable to suggest that some of the increase in the body mass measures in both groups of the present study was due to normal changes associated with puberty (15,17). Maturation effects may also partially explain why the relative changes in strength and power in the present study are greater than those previously reported in experienced strength trainers (19).…”
Section: Discussioncontrasting
confidence: 56%
“…Additional youth resistance training guidelines that include qualified supervision and an appropriate progression of training loads are available elsewhere. [35][36][37] An interesting anecdotal observation from this study is that children seemed to enjoy high repetition-moderate load training more so than low repetition-heavy load training.…”
Section: Muscular Endurancementioning
confidence: 99%
“…Such gains in strength can be attributed to neuromuscular "learning," in which training increases the number of motor neurons that will fire with each muscle contraction. 2,6,7 This mechanism helps explain strength gains from resistance training in populations with low androgen levels, including females and preadolescent males. Strength training can also augment the muscle enlargement that normally occurs with pubertal growth in males and females.…”
Section: Benefits Of Resistance Trainingmentioning
confidence: 99%
“…Strength training can also augment the muscle enlargement that normally occurs with pubertal growth in males and females. 3,6,8,9 Strength training can improve an adolescent athlete's performance in weight lifting and power lifting. Strength training is a common practice in sports like football in which size and strength are desirable.…”
Section: Benefits Of Resistance Trainingmentioning
confidence: 99%